2018
DOI: 10.1016/j.brs.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term efficacy of electroconvulsive stimulation in animal models of depression: The essential role of neuronal survival

Abstract: Altogether, these results reveal that increased synaptic connectivity and extended neuronal survival are key to the short and long-term efficacy of ECS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…Recently, extensive studies have suggested that ECT is highly effective in ameliorating depression symptoms with fewer unwanted effects (Liang et al, 2017(Liang et al, , 2018Karayagmurlu et al, 2019). Similar findings were also reported in animal studies using electroconvulsive seizures (ECS, an animal model for ECT) (Jonckheere et al, 2018;Alemu et al, 2019). Therefore, this review was aimed to interpret recent clinical and preclinical ECT studies and its potential mechanism on depression to provide clinicians and patients with greater appreciation of this approach to defeat depression.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Recently, extensive studies have suggested that ECT is highly effective in ameliorating depression symptoms with fewer unwanted effects (Liang et al, 2017(Liang et al, , 2018Karayagmurlu et al, 2019). Similar findings were also reported in animal studies using electroconvulsive seizures (ECS, an animal model for ECT) (Jonckheere et al, 2018;Alemu et al, 2019). Therefore, this review was aimed to interpret recent clinical and preclinical ECT studies and its potential mechanism on depression to provide clinicians and patients with greater appreciation of this approach to defeat depression.…”
Section: Introductionmentioning
confidence: 63%
“…Additionally, neuroplasticity triggered or enhanced by ECS administration significantly increased the number of mitochondria, synapses, and length of microvessels in depressed rats regardless of response (Chen et al, 2018). Employed with MAP6 KO mouse, a genetic model of depression, Jonckheere et al (2018) demonstrated that synaptogenesis and neurogenesis compensated for behavioral deficits. ECS enhances the proliferation of adult hippocampal neuronal progenitors, and continuation ECS led to persistent behavioral and biological improvements.…”
Section: Ecs In Preclinical Studiesmentioning
confidence: 97%
See 3 more Smart Citations